Evaluating the dynamic employment effects of training programs in East Germany using conditional difference-in-differences - Annette Bergemann; Bernd Fitzenberger; Stefan Speckesser (Institute for the Study of Labor (IZA), 2005)
This study analyzes the employment effects of training in East Germany. We propose and apply an extension of the widely used conditional difference-in-differences evaluation method. Focusing on transition rates between nonemployment and employment we take into account that employment is a state dependent process. Our results indicate that using transition rates is more appropriate and informative than using unconditional employment rates as commonly done in the literature. Training as a first participation in a program of Active Labor Market Policies shows zero to small positive effects both on reemployment probabilities and on probabilities of remaining employed with notable variation over the different start dates of the program.
Keywords: C14; C23; H43; J64; J68; 330; evaluation of active labor market policy in East Germany; nonparametric matching; conditional difference-in-differences; employment dynamics; Ashenfelter's Dip; bootstrap; Arbeitsmarktpolitik; Weiterbildung; Wirkungsanalyse; Mikroökonometrie; Schätzung; Neue Bundesländer